2021
DOI: 10.3390/nu13010183
|View full text |Cite
|
Sign up to set email alerts
|

A Narrative Review on Sarcopenia in Type 2 Diabetes Mellitus: Prevalence and Associated Factors

Abstract: Type 2 diabetes mellitus (T2DM) represents a major health burden for the elderly population, affecting approximately 25% of people over the age of 65 years. This percentage is expected to increase dramatically in the next decades in relation to the increased longevity of the population observed in recent years. Beyond microvascular and macrovascular complications, sarcopenia has been described as a new diabetes complication in the elderly population. Increasing attention has been paid by researchers and clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
155
2
16

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 216 publications
(213 citation statements)
references
References 122 publications
9
155
2
16
Order By: Relevance
“…These results indicate that patients with high levels of Cre/CysC may have better postprandial glucose disposal ability, even though they showed no differences in pancreatic function and insulin sensitivity. The present study did show a correlation between Cre/CysC and HbA1c, which is consistent with previous epidemiological studies showing that HbA1c is not associated with sarcopenia in type 2 diabetes individuals [3]. However, a relationship between glucose control and sarcopenia cannot be completely excluded.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These results indicate that patients with high levels of Cre/CysC may have better postprandial glucose disposal ability, even though they showed no differences in pancreatic function and insulin sensitivity. The present study did show a correlation between Cre/CysC and HbA1c, which is consistent with previous epidemiological studies showing that HbA1c is not associated with sarcopenia in type 2 diabetes individuals [3]. However, a relationship between glucose control and sarcopenia cannot be completely excluded.…”
Section: Discussionsupporting
confidence: 93%
“…A recent systematic review including 1,832 patients with type 2 diabetes and 4,694 euglycaemic subjects demonstrated that patients with type 2 diabetes have a higher risk of sarcopenia (OR: 1.55, [95% CI: 1.25-1.91]). Considering its heavy impact on quality of life and increased risk of fracture, disability and mortality, sarcopenia is emerging as a third category of diabetic complication [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Patients with type 2 diabetic kidney disease often show a series of metabolic and nutritional changes linked both to diabetes and kidney failure, including insulin resistance and cardiovascular comorbidities ( 80 ), protein-energy wasting and sarcopenia ( 81 ). These patients undergo an increase in MPD, an effect primarily mediated by the ubiquitin-proteasome pathway ( 82 , 83 ). On a kinetic basis, an increase in MPD is often associated with an increase in MPS.…”
Section: Aging and Common Kidney Disease Comorbidities Which Impair Mpsmentioning
confidence: 99%
“…The prevalence of sarcopenia in diabetes has been extensively investigated. In a recent narrative review, the prevalence of sarcopenia varied between 7% and 29% [ 21 ], according to age and metabolic control, but higher figures are frequently reported. A systematic review with meta-analysis including 15 studies confirmed a prevalence varying up to 50% [ 22 ], again driven by age and metabolic control.…”
Section: Methods and Areas Of Researchmentioning
confidence: 99%
“…A study with BIA concluded that patients with T2D have an enlarged ectopic fat at the expense of skeletal muscle, i.e., relative sarcopenia [ 23 ], and lower muscle mass is coupled with decreased muscle strength [ 24 ], also predicting diabetes in the general population [ 25 ]. The contribution of diabetes duration remains controversial [ 21 , 22 ], but older patients with T2D, with an expected longer duration of disease, show a larger decline in appendicular lean mass, muscle strength, and functional capacity compared with normoglycemic controls [ 26 ]. Notably, when compared with matched control populations, the risk of sarcopenia increased systematically in the presence of T2D (odds ratio (OR) 1.55; 95% confidence interval (CI) 1.25–1.91; p < 0.001 [ 22 ] and OR 1.63; 95% CI 1.20–2.22; p = 0.002 [ 27 ]).…”
Section: Methods and Areas Of Researchmentioning
confidence: 99%